Effects of Maternal Tobacco Smoke or Alpha Lipoic Acid on Puberty Onset, Estrous Cycle and Gonadotropin Levels in Female Rats - Ulker, Nazife; Yardimci, Ahmet; Kaya, Nihat; Tektemur, Ahmet; Akkoc, Ramazan Fazil; Guzel, Elif Erdem; Ozan, Enver (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY